2009
DOI: 10.3892/ijo_00000198
|View full text |Cite
|
Sign up to set email alerts
|

Cancer stem cells from human glioma cell line are resistant to Fas-induced apoptosis

Abstract: Abstract. Glioblastoma is the most common primary brain tumor, characterized by its resistance to treatments. To define efficient therapy, the origin of tumor-forming cells needs to be elucidated in order to search for new therapeutic pathways. The objective of this study was to determine the different cell populations constituting a human glioblastoma cell line, U-87 MG and their sensitivity to apoptosis induced through the activation of Fas, a membranous death receptor. By a cell sorting method, the sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 38 publications
(74 reference statements)
1
7
0
Order By: Relevance
“…We wondered whether the biophysical changes revealed by SdFFF analysis could help us to distinguish among sub-cellular populations, especially CSCs. As expected, and as already published [ 28 ], the F3 U87pLKO cell fraction exhibited more CSCs markers as compared with cells of the F1 fraction (data not shown). In the cell line in which autophagy was down-regulated (U87shBeclin1), analysis of CSCs markers confirmed a weak enrichment of the F3 fraction, based on enhancement of LGR5 and POU5F1 expressions (*p<0.05 and **p<0.01 respectively, Figure 6A ).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…We wondered whether the biophysical changes revealed by SdFFF analysis could help us to distinguish among sub-cellular populations, especially CSCs. As expected, and as already published [ 28 ], the F3 U87pLKO cell fraction exhibited more CSCs markers as compared with cells of the F1 fraction (data not shown). In the cell line in which autophagy was down-regulated (U87shBeclin1), analysis of CSCs markers confirmed a weak enrichment of the F3 fraction, based on enhancement of LGR5 and POU5F1 expressions (*p<0.05 and **p<0.01 respectively, Figure 6A ).…”
Section: Resultssupporting
confidence: 91%
“…Thus, larger and less dense cells generating more hydrodynamic lift forces within the mobile phase and not very sensitive to centrifugal force (blue cells on Figure 5A ), will be eluted before smaller and denser cells (red cells, Figure 5A ) generating less hydrodynamic forces and more sensitive to the multigravitational field. As for a number of other cell models [ 27 , 29 , 31 ], we found that under the elution conditions, U87 cells were eluted under the hyperlayer elution mode [ 28 , 30 ] schematized in Figure 5A .…”
Section: Resultsmentioning
confidence: 78%
See 3 more Smart Citations